Effects of Acceptance and Commitment Training on Treatment Integrity Amongst Behavioral Technicians. Issue 3 (May 2023) - Ragulan, Swathi; Bertoli, Erin; Shinall, Jacqueline A.; Kahng, SungWoo
Behavioral technicians (BT) within the field of applied behavior analysis may be at greater risk for experiencing burnout and stress due to the nature of their clients, job demands, and work environments. Burnout and stress may negatively impact BT's work performances, more specifically, their treatment integrity. Acceptance and Commitment Training (ACT) may be a useful tool to address the private events as well as the covert and overt behaviors associated with burnout and stress. The purpose of this study was to investigate the effects of an ACT intervention on improving treatment integrity and reducing work-related burnout and stress amongst BTs. Four BTs participated in an ACT workshop, and their treatment integrity as well as their burnout and stress levels were measured prior to and following the ACT workshop. Treatment integrity increased for all participants, suggesting that ACT-based interventions may be an effective approach to improving work performance (i.e., treatment integrity) amongst BTs who may experience workplace burnout and stress.